2022
DOI: 10.1155/2022/3201644
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Neuron-Glia in Neurological Disorders: At a Glance

Abstract: Based on the diverse physiological influence, the impact of glial cells has become much more evident on neurological illnesses, resulting in the origins of many diseases appearing to be more convoluted than previously happened. Since neurological disorders are often random and unknown, hence the construction of animal models is difficult to build, representing a small fraction of people with a gene mutation. As a result, an immediate necessity is grown to work within in vitro techniques for examining these ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 324 publications
0
14
0
Order By: Relevance
“…Although the current neurobiological mechanism of opioid abuse is primarily related to synaptic plasticity of dopaminergic and glutaminergic neurons, this drug-induced plasticity may also be enhanced by glial cell activity. More and more evidence showed that glial cells, including oligodendrocytes, astrocytes and microglia, participate in cognitive impairment-and drug-induced neuronal plasticity changes, through the activity of cytokines and neurotrophins ( Rahman et al, 2022 ). Chronic morphine therapy induces activation of astrocytes and microglia ( Valentinova et al, 2019 ).…”
Section: Rho Gtpases and Substance Dependencementioning
confidence: 99%
“…Although the current neurobiological mechanism of opioid abuse is primarily related to synaptic plasticity of dopaminergic and glutaminergic neurons, this drug-induced plasticity may also be enhanced by glial cell activity. More and more evidence showed that glial cells, including oligodendrocytes, astrocytes and microglia, participate in cognitive impairment-and drug-induced neuronal plasticity changes, through the activity of cytokines and neurotrophins ( Rahman et al, 2022 ). Chronic morphine therapy induces activation of astrocytes and microglia ( Valentinova et al, 2019 ).…”
Section: Rho Gtpases and Substance Dependencementioning
confidence: 99%
“…This process is called demyelination. Messages that pass along a demyelinated nerve become delayed or blocked [19].…”
Section: Neuron Damage Parametersmentioning
confidence: 99%
“…2020; Lago-Baldaia et al . 2020; Rahman et al . 2022), they have received rather little attention in the effort to unravel WDFY3 -associated pathomechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Currently an increasing number of studies concentrate on loss of WDFY3/Bchs and its effects on the nervous system with a focus on neuronal impairment. Although glial cells are known to play an essential role for neuronal function and neurodevelopment (Bittern et al 2021;Kim et al 2020;Lago-Baldaia et al 2020;Rahman et al 2022), they have received rather little attention in the effort to unravel WDFY3-associated pathomechanisms. So far, it was shown that loss of Wdfy3 is accompanied with mislocalisation of glial guidepost cells, which provide guidance cues for the formation of axonal tracts (Dragich et al 2016).…”
Section: Introductionmentioning
confidence: 99%